RISK REDUCTION IN SCHOOLS IN DISASTER-PRIED AREAS IN WETLAND ENVIRONMENT BANJAR DISTRICT - Herry Poda Nugroho Putro; Eva Alviawati; syarifuddin syarifuddin (JURNAL SOCIUS, 2021)
The research location is in Middle School Sungai Tabuk 3 and Sungai Tabuk 4. Sungai Tabuk is a sub-district in Banjar Regency with a high threat level of floods and forest and land fires. Data collection through questionnaires, observation, and tests competence students. Data analysis with t test. The results showed 140 social studies teachers in Banjar Regency 56.6% had integrated natural disasters in social studies learning, the model developed was modified scientific inquiry learning frompre-disaster, disaster events, and post-disaster. There is an increase in student competence regarding disaster risk reduction, where t (count)> t (table) on trials first at SMPN 4 with trials second at SMPN 3. These findings lead to the conclusion that learning scientific with effective inquiry for student disaster risk reduction, relevant for social studies learning, relevant to increasing student activity, an effective inquiry model for improving the quality of social studies learning processes and products in junior high schools. The findings of this study have positive implications for the development of social studies learning about natural disasters in junior high schools. The practical implications of the findings of this study are an increase in the ability of social studies teachers and the socialization of inquiry models for reductionrisk disaster in Junior High School